A bibliometric analysis of digital advertising in social media: the state of the art and future research agenda - Subhajit Pahari; Anupam Bandyopadhyay; Vijay Kumar V. M.; Sameer Pingle (Cogent Business & Management, 2024)
This study provides a comprehensive bibliometric analysis of social media digital advertising, examining 474 journal articles published between 2000 and 2023. Utilizing R programming and VOSviewer software, it uncovers a rapidly expanding field centered on consumer behavior and brand engagement. The analysis highlights influential works that demonstrate the strong connection between social media ads and consumer behavior. Key journals and conferences known for high-quality research are identified, with dominant keywords including 'consumer behavior,' 'brand engagement,' and 'marketing strategy.' The study notes a growing application of data analytics, artificial intelligence (AI), and augmented reality (AR) to enhance advertising effectiveness. It also addresses the social implications of advertising, acknowledging its capacity to shape behavior and raise ethical concerns. For businesses, insights from this study can aid in navigating the evolving landscape of social media advertising, especially with data analytics and AI. This research stands out for its focus on social media digital advertising and its rigorous methodology, offering an in-depth overview of trends, significant research, and future directions. The findings emphasize the increasing role of data analytics, AI, and AR, providing practical guidance for businesses looking to refine their digital advertising strategies in a dynamic social media environment.